MODEL GEOLOGI BAWAH PERMUKAAN DAERAH MUARAWAHAU HASIL ANALISIS ANOMALI GAYA BERAT BERDASARKAN ESTIMASI KEDALAMAN DENGAN METODE ANALISIS SPEKTRAL - Setyanta, Budi; Setiadi, Imam; Simamora, W.H. (Jurnal Geologi dan Sumberdaya Mineral, 2008)
A Study about a depth estimation on a gravity model in Muarawahau quadrangle, East Kalimantan, by using a Spectral Analysis method is very helpful to reduce ambiguity that appears in each modeling. The qualitative analysis shows that high anomalies lay at the eastern part of  the research area with values between  10 - 55 mgal, while low gravity anomalies between  -60 to 9 mgal lay at the western area. Two groups of anomaly in this area reflect a basin and basement high which is separated by a regional strike slip fault . A Model resulted  from  East to West  profiling and supported by a Spectral Analyses Method shows that the basin is constructed by PreTertiary rocks with density of about 2.6 gr/cc and thickness approximately 5 km, experiencing tectonic deformation. The eastern high anomaly block is the reflection of ultramafik rocks and mélange with the density of about 2.65 gr/cc. Rocks in this block is partly covered by volcanic sediments abaut 500 meter thich (2.3 gr/cc). However based on the values of anomaly, those two blocks are still underlined by the same granitic continent, meanwhile the existing ultramafic rocks are only ophiolite fragmen of oceanic crust. Keywords : Gravity anomaly, depth estimation, geological model.